PENGARUH PENGGUNAAN LKS BERBASIS POE DALAM PEMBELAJARAN IPA TERHADAP KOMPETENSI SISWA KELAS VII SMPN 5 PADANG - Ira Lestari Rifzal; Akmam Akmam; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2015)
Science learning should be do in process approach because science is not only the collection of fact but also process of discovery, so in the learning have to directed to application of the scientific method. An alternatif solution to solve this problem was to apply the student worksheet based POE (Predict, Observe and Explain). The purpose of this research was to find the effect of application student worksheet based POE in sciences learning the competence of students class VII SMPN 5 Padang. Type of this research was the quasi experiment with randomized control group only design. The population in this research were the students grade VII SMP 5 Padang who were registered in the 2014/2015 academic year. Sampling technique  was cluster random  sampling. Instruments of this research are test sheets of  learning  outcomes  for competence of cognitive, observation sheets for competence of attitudes, and skills assessment sheet for competence of skills.  The data of  three competences was analyzed and tried hypothesis use the chi squared. The result of hipotesys test for competence of cognitive, attitude and skill are x2count ≤ x2table at significance level 0,05 and dk 1 . Thus, it can be concluded that application student worksheet based POE in sciences learning the competence of students class VII SMPN 5 Padang give not signifikan effect